A Censual-Cartographic Analysis of Khamis M. Population Distribution: Interpreting Asir Census Buru Report, 1431H - Fayez, Fatemah Mohmmad (Journal of natural sciences, life and applied sciences, 2020)
GIS occupies a prominent place in the geographical arena. Has helped technical development in the field of cartography, one of those is to organize in the representation of natural and human geographical phenomena and to clarify the spatial relationships between those phenomena in a template A beautiful artistic and technical concept and style that is easy to understand. In some sources, this type of map is called statistical maps Due to the nature of the data and the quantitative methods that cartography depends on in its production. This study deals with the statistical data of the population in Khamis Mushait, and it was represented in some considerations on four maps This study was followed in its presentation and analysis of the four approaches (critical, analytical, experimental and applied). The study presented the definition of quantitative maps, their importance, the foundations of their classification, their types, the foundations of their construction and the methods of representation Al Cartography that you use, as the study dealt with quantitative maps in geographic information systems, and reviewed the most important The programs available for producing electronic maps are the most suitable and widely used types of representation symbols for representing geographical data Phenomena in every map. The study presented the applied steps used in producing quantitative maps in geographic information systems on population maps in Khamis Mushait governorate. The study also dealt with an inventory of the contents of the maps, their evaluation, analysis and classification in descending order according to the statistical data made available to the researcher. The problem of the study emerged in the lack of awareness of the vital role of geographic information systems and their various programs in producing maps Quantitative, and some reluctance to use and activate methods of location analysis on GIS maps and its various sources in the representation of phenomena on quantitative maps. The study found the importance of quantitative maps in geographic information systems and their high capabilities in producing and dealing with maps, the variation in their fields of display and the ease of application despite the lack of a number of graphical tools that can be applied in traditional methods and the need to link them, the limited use of GIS programs despite their cognitive importance and role. In building awareness of the place and the possibility of expanding its use, in addition to the need for the user and recipient of the map to have high skill and cognitive awareness sufficient to read and correctly interpret the components of the treasure and simulate reality. The study concluded with the results and recommendations.